Pemetaan Kerawanan Longsor Berbasis SIG: Implementasi Permen PU No. 22/PRT/M/2007 di Kabupaten Bengkulu Tengah - Muhammad Latif (Journal of Science, Technology, and Innovation, 2026)
This study develops a GIS-based landslide susceptibility mapping framework by operationalizing the weighting scheme prescribed in Indonesian Public Works Regulation No. 22/PRT/M/2007 within Bengkulu Tengah Regency. Seven physical parameters slope gradient, soil condition, lithology, rainfall intensity, slope hydrology, seismicity, and vegetation were standardized, scored, and integrated through weighted spatial overlay to produce a composite susceptibility index. Results reveal a regional dominance of low susceptibility, indicating systemic equilibrium among controlling parameters, while localized moderate to high zones reflect critical parameter interactions. Seismic influence functions primarily as a triggering modifier rather than a dominant determinant, whereas vegetation structure contributes mechanically to slope cohesion and hydrological regulation. The integrated model demonstrates methodological robustness by linking empirical spatial evidence with theoretical slope stability principles, ensuring analytical consistency and replicability. Conceptually, the framework advances landslide assessment from descriptive mapping toward predictive spatial evaluation. The findings support risk-informed land management strategies and highlight the utility of regulation-based multi-criteria GIS modeling as a scalable approach for hazard mitigation planning in geomorphologically dynamic regions.